Financialization and Financial Stability in Brasil. A Regulation Approach - Reither, Susanne (Momentum Quarterly, 2016)
The present Article discusses the trends of financialization in Brazil and their possible effects on the financial stability. Despite the relatively stable macro economic condition, the effect of the worldwide financial and economic crisis has been sudden and increasingly severe. This is due to the financialization, the fluctuations on the global financial market and the exchange rate fluctuations, which imply the performance of the brazilian economy in general. The brazilian government implemented a set of anti-cycle measures in order to counteract the effects of the crisis. Nevertheless the financialization processes remain. The financial expansion and the intensive integration of the brazilian financial market into the global market led to a high exposure of the brazilian economy and vulnerability of the international investors. This illustrates the difficulty of effective stabilizing policy choices considering the increasing financialization.